2019
DOI: 10.1038/s41598-019-47087-7
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology and network pharmacology of frailty reveal novel epigenetic targets and mechanisms

Abstract: Frailty is an age-associated condition, characterized by an inappropriate response to stress that results in a higher frequency of adverse outcomes (e.g., mortality, institutionalization and disability). Some light has been shed over its genetic background, but this is still a matter of debate. In the present study, we used network biology to analyze the interactome of frailty-related genes at different levels to relate them with pathways, clinical deficits and drugs with potential therapeutic implications. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These can result in gene expression silencing in DNA repair and anti-inflammatory genes [ 31 ]. It has also been suggested that other genes participating in the maintenance of muscle and nervous systems processes, chromatin remodeling, and transcription control may also be affected [ 32 ]. It has been proposed that these global changes in DNA methylation are associated with the incomplete restoration of epigenetic patterns after DNA replication or DNA repair [ 33 ], which contribute to the accumulation of epimutations in the bulk DNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These can result in gene expression silencing in DNA repair and anti-inflammatory genes [ 31 ]. It has also been suggested that other genes participating in the maintenance of muscle and nervous systems processes, chromatin remodeling, and transcription control may also be affected [ 32 ]. It has been proposed that these global changes in DNA methylation are associated with the incomplete restoration of epigenetic patterns after DNA replication or DNA repair [ 33 ], which contribute to the accumulation of epimutations in the bulk DNA.…”
Section: Resultsmentioning
confidence: 99%
“…The main interventions developed to date to improve frailty-related health outcomes include lifestyle/behavioral factors: exercise, nutrition, multicomponent interventions, individually-tailored geriatric care models and cognitive health maintenance [ 32 , 100 ]. Among them, exercise is considered the most effective intervention in preclinical and clinical models of frailty [ 103 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Still, some existing drugs affect multiple pathways involved in frailty including apoptosis, proteolysis, muscle proliferation and inflammation, e.g. existing antirheumatic agents modulate both the glucocorticoid receptor and ACE-involved targets [143]. Other novel anabolic agents such as selective androgen receptor modulators [144], and ghrelin mimetics are still under investigation to tackle muscle and bone loss [139].…”
Section: Role Of Pharmaceutical Agents In Managing Frailtymentioning
confidence: 99%
“…A critical role of these small molecules has been documented relative to the frailty-associated phenotypes, i.e., in muscle development and homeostasis [ 64 ], but also in neuronal processes such as brain development, synaptic plasticity, and learning and memory functions [ 65 ]. A study of network biology, by analyzing the interactome of frailty-related genes, prioritized 10 miRNA markers indirectly associated with frailty through the association of their targets [ 66 ]. To date, only three studies directly evaluated changes in blood plasma miRNAs in frail/non frail subjects [ 67 , 68 , 69 ].…”
Section: Search For Novel Biomarkers Of Frailty: the Role Of Mirnasmentioning
confidence: 99%